Pengaruh PAD dan DAU Melalui Belanja Modal Terhadap Pertumbuhan Ekonomi pada Kabupaten/Kota Provinsi Kalimantan Selatan (Periode 2011-2018) - Kurniawati Kurniawati; Muzdalifah Muzdalifah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This research was conducted to (1) Determine the effect of the Regional Original Revenue and General Allocation Funds for Capital Expenditures. (2) Determine the effect of the Regional Original Revenue, General Allocation Funds, and Capital Expenditures on the Economy. This research is a quantitative study using the Simultaneous Equation Model with Eviews 10 Two-Stage Least Square (TSLS) method. The data used in the study were sourced from the Central Statistics Agency of South Kalimantan Province and the Directorate General of Fiscal Balance 2011-2018.The results of phase 1 research with the best model Fixed Effect Model show that simultaneously Regional Original Revenue and General Allocation Funds significantly affect capital expenditure. However, the Regional Original Revenue variable partially has no significant effect on capital expenditure. While the second stage of research with the best model Random Effect Model shows the results that simultaneously or partially, the variables of Regional Original Revenue, General Allocation Funds, and predictive Capital Expenditures have a significant effect on Economic Growth.